Toward a Model of Functional Brain Processes II: Central Nervous System Functional Macro-architecture. - Bickhard, Mark (Axiomathes: Global Philosophy, 2015)
The first paper in this pair (Bickhard in Axiomathes, ) developed a model of the nature of representation and cognition, and argued for a model of the micro-functioning of the brain on the basis of that model. In this sequel paper, starting with part III, this model is extended to address macro-functioning in the CNS. In part IV, I offer a discussion of an approach to brain functioning that has some similarities with, as well as differences from, the model presented here: sometimes called the Predictive Brain approach.